Establishment of sensory characteristics of locally made peanut butter hydrogenated vegetable oil as stabilizer - Lomongo, Bella Sue Janis Q.
ABSTRACT The acceptability to consumer of peanut butter manufactured using hydrogenated vegetable oil as stabilizer was determined. Untrained panelists evaluated, peanut flavor, roasted peanut flavor, consistency, and spreadability of peanut butter samples using 150-mm unstructured line scales. Analysis of Variance was used to determine significant differences among samples at 5% level of significance. Samples with significant differences were further subjected to Duncan Multiple Range Test to identify which among the samples were significantly different from the others. Result indicated significant effect of roasting time on all attributes evaluated. At 50 minute roasting time, samples exhibited the most acceptable characteristics such as distinct peanut and roasted peanut flavor, brown color among samples, a moderately thick consistency, and a slightly spreadable peanut paste. At 60 minute roasting time, samples had slightly distinct peanut flavor, dark brown color, moderately strong roasted peanut flavor, moderately thick consistency and spreadable. At 40 minutes, samples had slightly distinct peanut flavor, moderately distinct roasted peanut flavor, slightly pale brown color, slightly thin consistency and spreadable. Results showed that conditioning and level of stabilizer had no significant effect on the acceptability of peanut butter samples.